REBRANDING MSME PRODUCTS AS A VISUAL IDENTITY IN INCREASING BRAND AWARENESS THROUGH SWOT ANALYSIS - Sutrisno Sutrisno; Supartono Supartono; Sufyati HS; Didit Hadayanti; Achirsyah Bahar (SEAN Institute, 2023)
Rebranding MSME items as a visual identity is important to boost brand awareness. Through rebranding, the visual identity of a product can be improved, making the product easier for consumers to remember and improving the positive image of the product. Rebranding is an essential technique for increasing brand awareness and the success of micro, small, and medium-sized enterprises. This study rebranded a product logo for one of the MSMEs in the cake business that relies solely on Whatsapp sales and uses product images as its business visual identity mark. The SWOT analysis approach is used to examine the rebranding needs of a product in order to accommodate the company's strengths, weaknesses, opportunities, and threats. Based on the results of the SWOT analysis, the research recommends redesigning the product, particularly in terms of the logo, by employing a simple and memorable logo concept that is easily recalled by consumers for the purpose of enhancing brand awareness. With this logo redesign, it is intended that it would enhance client interest to MSME enterprises.